PEMBUATAN FILM INDIKATOR pH ASAM BASA DARI EKSTRAK BUAH MURBEI (Morus alba L) BERBASIS KITOSAN - Anis Susanti; Husna Amalya Melati; Lukman Hadi (Universitas Tanjungpura, Prodi Pendidikan Kimia, 2020)
Morus alba L species, usually known as mulberry, have a distinctive color, namely blackish purple. This color is caused by the presence of anthocyanin compounds which are color pigments. Anthocyanin compounds have the potential to be used as indicators of acid base. This study aims to determine the pH, solubility and shelf life trails of acid-base indicator films from chitosan-based mulberry fruit extracts. The method used is extraction by maceration, through immersion of mulberry fruit that has been refined using 96% ethanol solvent. Determination of the pH route using an acetate buffer solution with a pH of 1-14. The solubility of acid-base indicator film can be seen by immersing the indicator film in water for 24 hours, weighing it to a constant and comparing it to film that is not immersed in water and calculated the value of FS% (film solution). The shelf life of the indicator film was observed using a microscope to find out whether there was mold growth on the surface of the film. The results of the study showed that the pH of the acid-base indicator film strain of mulberry fruit extract, namely, pH 1-3 were red, and pH 10-14 were green. Based on data analysis, the percentage of the solubility of the acid-base indicator film of mulberry extract was 40.18%, which means that the indicator film with mulberry extract was hydrophilic so that it was easily dissolved in water compared to without the mulberry extract of 22.2% which had lower solubility values. Durability for 30 days was observed in the absence of growth of microorganisms / fungi on the surface of the indicator film.